STAIR: A generic and fully-automated method to fuse multiple sources of optical satellite data to generate a high-resolution, daily and cloud-/gap-free surface reflectance product - Luo, Yunan; Guan, Kaiyu; Peng, Jian (Remote sensing of environment, 2018)
Surface reflectance data with high resolutions in both space and time have been desired and demanded by scientific research and societal applications. Standard satellite missions could not provide such data at both high resolutions. Fusion approaches that leverage the complementary strengths in various satellite sources (e.g. MODIS/VIIRS/GOES-R's sub-daily revisiting frequency and Landsat/Sentinel-2's high spatial resolution) provide a viable means to simultaneously achieve both high resolutions in the fusion data. In this paper, we presented a novel, generic and fully-automated method, STAIR, for fusing multi-spectral satellite data to generate a high-frequency, high-resolution and cloud-/gap-free data. Building on the time series of multiple sources of satellite data, STAIR first imputes the missing-value pixels (due to cloud cover or sensor mechanical issues) in satellite images using an adaptive-average correction process, which takes into account different land covers and neighborhood information of miss-value pixels through an automatic segmentation. To fuse satellite images, it employs a local interpolation model to capture the most informative spatial information provided by the high spatial resolution data (e.g., Landsat) and then performs an adjustment step to incorporate the temporal patterns provided by the high-frequency data (e.g., MODIS). The resulting fused products contain daily, high spatial resolution and cloud-/gap-free fused images. We tested our algorithm to fuse surface reflectance data of MODIS and Landsat in Champaign County at Illinois and generated daily time series for all the growing seasons (Apr 1 to Nov 1) from 2000 to 2015 at 30 m resolution. Extensive experiments demonstrated that STAIR not only captures correct texture patterns but also predicts accurate reflectance values in the generated images, with a significant performance improvement over the classic STARFM algorithm. This method is computationally efficient and ready to be scaled up to continental scales. It is also sufficiently generic to easily include various optical satellite data for fusion. We envision this novel algorithm can provide effective means to leverage historical optical satellite data to build long-term daily, 30 m surface reflectance record (e.g. from 2000 to present) at continental scales for various applications, as well as produce operational near-realtime daily and high-resolution data for future earth observation applications. •A generic and fully-automated method to fuse multi-source optical satellite data•Generation of a daily, 30-meter and cloud-/gap-free surface reflectance time series•The new algorithm, STAIR, outperforms the classic STARFM in various metrics.•Computationally efficient and ready to be scaled up to continental scales